Modelling the volatility of commodities prices using a stochastic volatility model with random level shifts. - Alvaro Polack, Dennis Leonardo (2015)
The volatility of commodities prices such as oil or minerals is an important issue for small and open economies that depends on raw materials. For example, in many countries of Latin America, the volatility of commodities can a¤ect operational cost or investment schedules of business related to the primary sector. At the macroeconomic level, a high volatility can provocate changes in the current account and in capital in ows, or, on the side of importers, increase uncertainty about production costs and in ation. Therefore, modeling volatility of commodities prices would be useful for private agents and policy makers. For the rst ones, it gives valuable information for better options contracts that allow hedge under big uncertainty, and for the second ones, it could help to a better understanding of business cycles given the correlation between mineral prices uctuations, capital in ows and investment expectations.